European Association of Urology Guidelines on Upper Urinary Tract Urothelial Carcinoma: Summary of the 2025 Update - Masson-Lecomte, Alexandra; Birtle, Alison; Pradere, Benjamin; Capoun, Otakar; Compérat, Eva; Domínguez-Escrig, José L; Liedberg, Fredrik; Makaroff, Lydia; Mariappan, Paramananthan; Moschini, Marco; Rai, Bhavan P; van Rhijn, Bas W G; et al. (European urology, 2025)
BACKGROUND AND OBJECTIVE: We present a summary of the 2025 update for the European Association of Urology (EAU) guidelines for upper urinary tract urothelial carcinoma (UTUC). The aim is to provide practical recommendations on the clinical management of UTUC with a focus on diagnosis, treatment, and follow-up. METHODS: For the 2025 guidelines on UTUC, new and relevant evidence was identified, collated, and appraised via a structured assessment of the literature. Databases searched included Medline, EMBASE, and the Cochrane Libraries. Recommendations within the guidelines were developed by the panel to prioritise clinically important care decisions. The strength of each recommendation was determined according to a balance between desirable and undesirable consequences of alternative management strategies, the quality of the evidence (including the certainty of estimates), and the nature and variability of patient values and preferences. KEY FINDINGS AND LIMITATIONS: Key recommendations emphasise the importance of thorough diagnosis, treatment, and follow-up for patients with UTUC. The guidelines stress the importance of appropriate treatment taking into account patient values and preferences. Key updates in the 2025 UTUC guidelines include: significant changes to the recommendations for UTUC diagnosis; complete revision of the sections addressing risk stratification, ureteroscopy, and the surgical approach for radical nephroureterectomy; addition of four new recommendations, two related to kidney-sparing management of localised low-risk UTUC and a further two related to management of high-risk nonmetastatic UTUC; a review and adaptation of recommendation for UTUC follow-up; and addition of a new section addressing quality indicators for UTUC management. CONCLUSIONS AND CLINICAL IMPLICATIONS: This overview of the 2025 EAU guidelines on UTUC offers valuable insights into risk factors, diagnosis, classification, treatment, and follow-up for UTUC. The guidelines contain information on the management of individual patients according to the current best evidence and are designed for effective integration in clinical practice.
Keywords: nádory močovodu; nádory ledvin; Urology; Management; Surgery; karcinom z přechodných buněk; Prognostic factors; Chemotherapy; společnosti lékařské; Europe; Kidney Neoplasms; Societies, Medical; Genetic screening; Ureter; Ureteral Neoplasms; Evropa; Immunotherapy; Urothelial carcinoma; lidé; Humans; (Neo)adjuvant therapy; Renal pelvis; urologie; Carcinoma, Transitional Cell